2017
DOI: 10.1159/000462962
|View full text |Cite
|
Sign up to set email alerts
|

Whole Genome Sequence Identified a Rare Homozygous Pathogenic Mutation of the DSG2 Gene in a Familial Arrhythmogenic Cardiomyopathy Involving Both Ventricles

Abstract: Background: This study was designed to identify the pathogenic mutation in a Chinese family with arrhythmogenic right ventricular cardiomyopathy/dysplasia (ARVC/D) using whole genome sequencing (WGS). Methods and Results: Probands II:1 and II:2 underwent routine examinations for diagnosis. Genomic DNA was extracted from the peripheral blood of family members and analyzed using WGS. A total of 60,285 single-nucleotide polymorphisms (SNP) and 13,918 insertions/deletions (InDel) occurring in the exonic regions of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
14
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 24 publications
1
14
0
Order By: Relevance
“…In 2009, a Dutch multicenter cohort reported that DSG2 and DSC2 gene are most frequently identified to be compound in patients with ARVC [16]. Meanwhile, some studies have reported recessive inheritance pattern of DSG2 in ARVC pedigree [17][18][19]. These results suggested that single heterozygous variant in DSG2 might not be sufficient to penetrate ARVC phenotype, which could explain asymptomatic relatives of proband carrying DSG2-p.Leu237Ter variant.…”
Section: Discussionmentioning
confidence: 99%
“…In 2009, a Dutch multicenter cohort reported that DSG2 and DSC2 gene are most frequently identified to be compound in patients with ARVC [16]. Meanwhile, some studies have reported recessive inheritance pattern of DSG2 in ARVC pedigree [17][18][19]. These results suggested that single heterozygous variant in DSG2 might not be sufficient to penetrate ARVC phenotype, which could explain asymptomatic relatives of proband carrying DSG2-p.Leu237Ter variant.…”
Section: Discussionmentioning
confidence: 99%
“…According to previous studies, the DSG2 p.N271S mutation in young transgenic mice (similar to the N266S mutation in humans) was associated with SCD induced by spontaneous VT, biventricular dilation and aneurysms, myocardial necrosis and heart failure [ 16 ]. According to previous report about a Chinese Han family with ARVC/D from our cardiac center, [ 17 ] we have identified a homozygous mutation of DSG2 p.F531C by the whole genome sequencing. The carriers of the homozygous genotype were shown to be affected with biventricular dilation and non-compaction, aneurysms in the left ventricle and spontaneous multifocal VTs.…”
Section: Discussionmentioning
confidence: 99%
“…A myocardial biopsy showed interrupted, atrophic and disarranged myocardial fibers; interstitial fibers, hyperplastic, infiltrated and collagen-invaded fibers and adipocytes; and widened and destroyed intercalated discs. Some carriers with heterozygous mutation of DSG2 p.F531C showed incomplete penetrance [ 17 ]. Similar phenotype of ARVC/D induced by homozygous mutation of DSG2 p.F531C was also found in another Chinese Han family and DSG2-F531C knock-in mice with decreased expression of CX43.…”
Section: Discussionmentioning
confidence: 99%
“…InDels were considered damaging, and nonsynonymous SNPs predicted by SIFT ( http://sift.jcvi.org/www/ ) (Kumar et al., 2009 ) and PolyPhen‐2 (Polymorphism Phenotyping v2, http://genetics.bwh.harvard.edu/pph2/ ) (Adzhubei et al., 2010 ). The mutations were screened in approximately 200 genes (shown in our previous study (Lin et al., 2017 )), associated with hereditary arrhythmias and cardiomyopathies. The filtering criteria for mutation inclusion were as follows: same mutations in the WES data; missense, nonsense, and InDel mutations; and SNPs with a minor allele frequency not more than 0.01, according to the NCBI SNP database (Smigielski et al., 2000 ; Via et al., 2010 ).…”
Section: Methodsmentioning
confidence: 99%